A 12-Week Randomized Controlled Trial of Twice-Daily Intranasal Oxytocin for Social Cognitive Deficits in People with Schizophrenia - Jarskog, L. Fredrik (Schizophr Res, 2017)
Social cognition is impaired in people with schizophrenia and these deficits are strongly correlated with social functioning. Oxytocin is a hypothalamic peptide that contributes to maternal infant bonding and has diverse pro-social effects in adults. This study tested the hypothesis that 12 weeks of intranasal oxytocin will improve social cognitive function in outpatients with schizophrenia and schizoaffective disorder. Sixty-eight eligible participants were randomized to oxytocin (24 IU twice daily) or placebo. Social cognitive function was assessed using the Emotion Recognition-40, Brüne Theory of Mind, Reading the Mind in the Eyes test, Trustworthiness task and Ambiguous Intentions Hostility Questionnaire at baseline, 6 weeks and 12 weeks. In addition, social function was assessed using the Specific Levels of Functioning Scale and a role-play test, and psychopathology was assessed using the Positive and Negative Syndrome Scale (PANSS). Fifty-five participants completed the 12-week trial. The study found no evidence for a differential advantage of oxytocin over placebo on social cognition. Among secondary outcomes, there was a modest advantage for oxytocin over placebo on a component of social functioning, although there was also evidence that the placebo group outperformed the oxytocin group on the role-play task. No between-group differences emerged on measures of psychopathology in pre-specified comparisons, but oxytocin showed significant within-group reduction in PANSS negative symptoms and significant between-group improvement in negative symptoms in the schizophrenia subgroup. Further testing is needed to clarify whether oxytocin has therapeutic potential for social cognitive deficits and/or negative symptoms in people with schizophrenia.